Contributing Factors and Challenges in Mastering Academic Writing Skills: Multiple Case Studies of Deaf Students in Inclusive Universities in Indonesia - Dianastiti, Firstya Evi; Suwandi, Sarwiji; Setiawan, Budhi (International Journal of Language Education, 2024)
The purpose of this research is to describe the challenges and factors causing difficulties of deaf students in mastering writing skills at inclusive universities in Indonesia. This research is focused in Central Java province because of the more universities are considered as inclusive universities. This research was conducted in September-December 2022. The subjects in this research were selected using the purposive sampling method. Based on these limits, 35 Deaf students from six inclusive universities were obtained as respondents. The data collection techniques used questionnaires, observations, interviews, and concentrated discussions. Furthermore, the data analysis steps undertaken consisted of: (a) data analysis, (b) data revision, and (c) data verification. The results of this research concluded that the challenges experienced by students were broadly related to: (a) difficulty in mastering vocabulary, (b) understanding punctuation, and (c) difficulty if mastering complex sentences. As for more specifically related to academic text writing skills, the obstacles experienced by students including: (a) composing effective sentences, (b) developing paragraphs, (c) paraphrasing techniques, (d) writing academic texts in accordance with linguistic rules, and (e) writing bibliography. Furthermore, factors causing the occurrence of the obstacles in the mastery of academic text writing skills including: (a) unaccessible learning resources, (b) less effectively interwoven communication during lectures, and (c) different sentence structure in Sign Language (Bisindo) with Indonesian sentence structure.